Evolution of the Interplanetary Turbulence and the Associated Turbulence Anisotropy in the Outer Heliosphere: VOYAGER 2 Observations - Xingyu Zhu; Jiansen He; Gary P. Zank; Daniel Verscharen; Ling-Ling Zhao; Die Duan; Rong Lin (The Astrophysical Journal, 2024)
We study the radial evolution of the inertial-range solar wind plasma turbulence and its anisotropy in the outer heliosphere. We use magnetic field ( B ) measurements from the Voyager 2 spacecraft for heliocentric distances R from 1 to 33 au. We find that the perpendicular and trace power spectral densities (PSDs) of the magnetic field ( ${E}_{{{\rm{B}}}_{\perp }}$ and ${E}_{{{\rm{B}}}_{Tr}}$ ) still follow a Kolmogorov-like spectrum until 33 au. The parallel magnetic field PSD, ${E}_{B_{\parallel }}$ , transits from a power-law index of −2 to −5/3 as the distance crosses R ∼ 10 au. The PSD at frequencies 0.01 Hz < f < 0.2 Hz flattens at R > 20 au, gradually approaching an f ^−1 spectrum, probably due to instrument noise. At 0.002 Hz < f < 0.1 Hz, quasi-parallel propagation dominates at 1 au < R < 7 au, with quasi-perpendicular propagation gradually emerging at R > 5 au. For R > 7 au, oblique propagation becomes the primary mode of propagation. At smaller frequencies of f < 0.01 Hz, ${E}_{{{\rm{B}}}_{\perp }}$ increases with propagation angle at 1 au < R < 5 au, and in contrast decreases with propagation angle at R > 5 au due to the enhanced power level at propagation angles smaller than 20°. Such enhancement may derive from the injection of wave energy from the pickup ion source into the background turbulent cascade, and the injected wave energy is transferred across scales without leaving local enhancements in ${E}_{{{\rm{B}}}_{\perp }}$ or ${E}_{{{\rm{B}}}_{Tr}}$ .